Knowledge level of the elementary school of Arjasari students after education regarding natural background radiation and oral health care - A, Azhari; Sitam, Suhardjo; Susilawati, Sri; Satifyl, Irmaleny; Octavia, Ivhatry Rizky; Damayanti, Merry Annisa (Universitas Padjadjaran, 2017)
Introduction: Environment and behaviour are the main factors affecting the health status of a human being. People living in high natural radiation exposure area (radon zone), which is as much as 85% of the air content, characterized by many presents of granite rocks. The village of Arjasari is an area with many granite rocks presence. The objective of this study was to determined the knowledge level of the elementary school students after education regarding natural background radiation and oral health care. Methods: The research was a descriptive survey research, with data sampling taken by using questionnaires towards as much as 150 elementary students. Previously, respondents were given first education regarding natural background radiation and oral health care. Instruments in this study using questionnaires that was tested for validation and reliabilities. Data analysis used was a descriptive survey technique processed by using computer program. Data was percentages of three rating categories, which were high, medium and low. Results: The results showed that the knowledge level of student regarding natural background radiation and oral health care. was as much as 14% in the high category; as much as 45% in the moderate category; and as much as 41% in the low category. Conclusion: Knowledge level of student after education about natural radiation and the effect of oral health was in the moderate category level.